2019
DOI: 10.1556/004.2019.012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tris (hydroxymethyl) aminomethane on the quality of frozen-thawed boar spermatozoa

Abstract: Tris (hydroxymethyl) aminomethane (Tris) has been used as a pH regulator for buffering the pH of dilution extenders for boar semen, such as the Modena extender. The purpose of the present study was to assess the effects of Tris supplementation at different concentrations (0, 8, 24 and 72 μM) into the freezing extender on the quality and fertilising capacity of frozen-thawed boar spermatozoa. The results showed that the supplementation of 24 μM of Tris gave significantly higher percentages of sperm viability an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…These kinetic parameters are directly related to the ability of the sperm to fertilize [ 35 ]. This efficiency may be related to the basic components of this medium, as TRIS has been used as an efficient pH regulator [ 36 ]. Furthermore, the phospholipids present in egg yolk have beneficial binding and protective properties for the plasma membrane [ 37 ], acting as non-permeable cryoprotectants [ 38 ] and protecting the functional integrity of sperm against thermal shock and cryoinjury [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…These kinetic parameters are directly related to the ability of the sperm to fertilize [ 35 ]. This efficiency may be related to the basic components of this medium, as TRIS has been used as an efficient pH regulator [ 36 ]. Furthermore, the phospholipids present in egg yolk have beneficial binding and protective properties for the plasma membrane [ 37 ], acting as non-permeable cryoprotectants [ 38 ] and protecting the functional integrity of sperm against thermal shock and cryoinjury [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fructose is the major carbohydrate source in bovine, including buffalo semen (Juyena & Stelletta, 2012). Tris (hydroxymethyl) aminomethane is a universal buffer suitable for preserving semen from various livestock (Namula et al, 2019). The results showed that the three commercial diluents with different lecithin sources had the same ability to protect the sperm plasma membrane during freezing and thawing.…”
Section: Discussionmentioning
confidence: 99%
“…During semen cryopreservation, any changes in pH could affect the metabolism rates, motility, viability, and plasma membrane integrity [ 34 , 35 ]. Sodium citrate, HEPES, bicarbonate, and tris have been used as pH controllers to maintain the pH in the extender [ 9 , 19 , 25 ]. The pH of tris is representative of most living cells.…”
Section: Discussionmentioning
confidence: 99%
“…It has the advantage of being much less expensive than any other buffering agent and being highly soluble in water. In mammals, tris has been applied in the semen extender as a practical pH regulator that prevents the alteration of the hydroxide ion and hydronium ion concentration, protecting the cell against pH changes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation